Cuexcomate or temezcal?: deciphering the circular architectural features at Angamuco, Michoacán, Mexico - Ahrens, Corrie, author; Fisher, Christopher T., advisor; Leisz, Stephen, committee member; Didier, John, committee member (Colorado State University. Libraries, 2013)
The Middle Postclassic Purépecha site of Angamuco in the Lake Pátzcuaro Basin, Michoacán, Mexico possesses a significant number of circular architectural features. Comparison of these features to similar structures across Mesoamerica suggests their function as cuexcomates (granaries) or temezcals (sweatbaths). Based on comparative research of storage structures and sweatbaths employed throughout Mesoamerica, identification of physical attributes associated with cuexcomates and temezcals provided a basic foundation for identification of these structures during field survey. The availability of GPS and LiDAR data enable the use of spatial spatial statistics resulting in the identification of statistically significant spatial clustering of the circular features based on diameter. These clusters reside in elite and commoner residential and public/civic-ceremonial areas. Further inspection of these areas has provided insights into storage behavior, socio-economic characteristics, access, and urban development among the Purépecha. Future research at Angamuco providing the existence of additional circular features will aid in better identification of circular structure types and the expansion of storage knowledge and spatial analysis techniques employed at archaeological sites.
Keywords: circular; storage; architecture; Mesoamerica; Purépecha